Principles of water and wastewater treatment processes - Stuetz, R. (IWA Pub., 2009)
"Principles of Water and Wastewater Treatment Processes outlines the principle unit operations that are involved in the separation, degradation and utilsation of organic and inorganic matter during water and wastewater treatment. It is designed for individual, self-paced study that describes the form, function and application of unit operations for the treatment of water and wastewater. Each section of the text provides step-by-step learning, the key points that highlight the principles involved, exercises to aid understanding, self-assessment questions, text references. It is organised so that the reader can learn in their own time."--Back cover
Previous version published: 2003 with the same ISBNs.
Keywords: Water -- Purification.; Sewage -- Purification.; elektronické knihy; electronic books